Kepemimpinan Kepala Sekolah - Latifa Hasana; Wiwil Anggraini; Tiara Astika sari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The success of a school is greatly influenced by the role of the principal's leadership in managing educational resources and guiding teachers and school staff towards achieving optimal educational goals. Principal leadership includes the ability to plan, organize, motivate, and direct all potentials in the school to achieve quality education. The principal as a leader is not only tasked with administrative aspects, but also plays an important role in creating a conducive learning climate, supporting innovation in teaching, and improving teacher competence. This article discusses the concept, role, and challenges faced by principals in implementing leadership in schools, as well as strategies that can be applied to improve school performance. With effective leadership, principals are able to bring positive changes to the progress of education in their schools.